O Programa Nacional do Livro Didático para o ensino médio - PNLD: uma análise a partir dos livros didáticos de Geografia - Silva, Micaelle Amancio Da (2018)
This dissertation analyzes the relation between the National Textbook Program for High School and School Geography, in order to find out if the requirements of this program, established in the convocation notices for the registration of didactic works, have promoted effective changes in the textbook of this discipline, destined to this modality of education. The National Textbook Program, which was established as a State policy, was implemented in Brazil in 1985, undergoing some changes in its operation over the years. Among them, the implementation of the evaluation system, in 1996, with the purpose of acquiring quality books for distribution in public schools. But it is also a power action of the State, because we understand that the said Program, through the evaluation criteria established in the edict, influences the production of the didactic book, consequently in the books of Geography. For the development of this research, we carried out a review of the literature, to build our theoretical contribution, in authors who discuss the theme and related topics. Based on this reasoning, based on documentary and content analysis (BARDIN, 1977), we analyzed the call announcements of the 2007/09, 2012 and 2015 selections, identifying their goals, changes and permanencies. In order to later analyze the Geography textbooks of the collections such as Território e Sociedade no Mundo Globalizado, Fronteiras da Globalização e Geografia Geral e do Brasil, verifying their conformity with the determinations expressed in the respective edicts. In this, we find that the books analyzed here, to a certain extent, were adapting the directives established in the edicts, being produced from the requirements of the mentioned Program, influencing in the Geography recommended in these manuals, consequently in the school discipline, in view, the importance that this resource acquired in the classroom. However, the books presented flaws, mainly regarding the theoretical- methodological aspects, that brought limits to the teaching-learning process, evidencing the incoherence between the established criteria and the evaluation process. Thus, we consider that school geography should be understood from all the elements that surround it, including the textbook and its public policies.